2003
DOI: 10.1080/15572536.2004.11833050
|View full text |Cite
|
Sign up to set email alerts
|

Dyrithiopsis lakefuxianensisgen. et sp. nov. from Fuxian Lake, Yunnan, China, and notes on the taxonomic confusion surroundingDyrithium

Abstract: A new taxon with Dyrithium-like characteristics was collected from Lake Fuxian in China. The taxon is typical of the Amphisphaeriaceaein that it has relatively large, ostiolate, immersed ascomata, unitunicate asci with a J + subapical ring, and brown ascospores. It is similar to Dym'thium in that it has muriform ascospores, but considerable confusion surrounds this genus. In Dyrithium asci are bitunicate and lack a J + subapical ring, while this was not true of our species. A new genus, Dyrithiopsis, therefore… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2007
2007
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 7 publications
0
6
0
Order By: Relevance
“…PCR amplifications were conducted as outlined by Jeewon et al . 38,39 and PCR products were sequenced by GenScript Biotechnology Co., Nanjing, China.…”
Section: Methodsmentioning
confidence: 99%
“…PCR amplifications were conducted as outlined by Jeewon et al . 38,39 and PCR products were sequenced by GenScript Biotechnology Co., Nanjing, China.…”
Section: Methodsmentioning
confidence: 99%
“…Jeewon et al 2003Jeewon et al , 2017Ariyawansa et al 2015;Liu et al 2015;Hyde et al 2017a, b;Tibpromma et al 2017;Wanasinghe et al 2017Wanasinghe et al , 2018Jayawardena et al 2018a, b). The use of other molecular approaches based on DNA sequence data (e.g.…”
Section: Using Mgdna From Environment In Species Identificationmentioning
confidence: 99%
“…Hyde, while Luo et al (2004) reported fungi from Dianchi Lake. Many new taxa have since been described including several new genera (Inderbitzin 2000, Jeewon et al 2003, Cai et al 2005, Cai & Hyde 2007, Wongsawas et al 2009a, b , Hu et al 2012, Liu et al 2015, Su et al 2015, 2016a, b, Luo et al 2016, 2017, Wang et al 2016, Zhu et al 2016. Hu et al (2013) also published a review paper of aquatic fungi in China.…”
Section: Introductionmentioning
confidence: 99%
“…About ten years later, mycologists started to investigate the lignicolous freshwater fungi in Hong Kong and reported many new taxa (Tsui et al 1997, 2000, 2001a, b, 2003, Goh et al 1998, Hyde & Goh 1998, Ranghoo & Hyde 1998, Ho et al 1999. In mainland China, investigations of lignicolous freshwater fungi mostly focused in the south to southwestern regions (Inderbitzin 2000, Jeewon et al 2003, Cai et al 2005, Hu et al 2013. Cai et al (2002) investigated the fungal diversity in Fuxian Lake in Yunnan Province and reported 64 higher fungi, with a new ascomycete Pseudohalonectria fuxianii L. Cai, K.M.…”
Section: Introductionmentioning
confidence: 99%